2023
DOI: 10.1021/acs.orglett.3c02265
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Inverse-Electron-Demand Cycloaddition Reactions Controlled by Frontier Molecular Orbital Interactions

Dennis Svatunek,
Konrad Chojnacki,
Titas Deb
et al.

Abstract: Chemoselective pairs of bioorthogonal reactants enable the simultaneous labeling of several biomolecules. Here, we access orthogonal click reactions by exploiting differences in frontier molecular orbital interaction energies in transition states. We establish that five-membered cyclic dienes are inert to isonitriles but readily react with strained alkynes, while tetrazines with bulky substituents readily react with isonitriles. Strained alkynes show an opposite reactivity pattern. The approach was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Expanding on this understanding, Svatunek et al demonstrated that while isonitriles quickly react with tetrazines that have significant steric demands, they remain unreactive with dienes like tetrachlorocyclopentadienone ethylene ketal (TCK) or 4,4-difluoro-3,5-diphenyl-4H-pyrazole (DFP) [ 129 ]. The reactivity of these dienes with strained alkynes is discussed in section 4.3.…”
Section: [4 + 2] Cycloadditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding on this understanding, Svatunek et al demonstrated that while isonitriles quickly react with tetrazines that have significant steric demands, they remain unreactive with dienes like tetrachlorocyclopentadienone ethylene ketal (TCK) or 4,4-difluoro-3,5-diphenyl-4H-pyrazole (DFP) [ 129 ]. The reactivity of these dienes with strained alkynes is discussed in section 4.3.…”
Section: [4 + 2] Cycloadditionsmentioning
confidence: 99%
“…47 Orthogonality between isonitrile/tetrazine and BCN/TCK cycloadditions. TCK Tetrachlorocyclopentadienone ethylene ketal Reprinted with permission from [ 129 ] …”
Section: [4 + 2] Cycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying two proteins with either a bulky DTTz or tetrachlorocyclopentadienone ethylene ketal (TCK) FMCD allowed selective protein modification using an isonitrile and a BCN, respectively (Fig. 18 ) [ 118 ]. In this example, the fluorophore was conjugated to the isonitrile.…”
Section: Tuning the Reaction Partners For Dual And Triple Orthogonal ...mentioning
confidence: 99%